Langmuir probe measurements and mass spectrometry of plasma plumes generated by laser ablation of La0.4Ca0.6MnO3 - LUNNEY, JAMES GERARD (My University, 2014)
The plasma formed in vacuum by UV nanosecond laser ablation of La0.4Ca0.6MnO3 in the fluence range of 0.8 to 1.9 J cm−2 using both Langmuir probe analysis and energy-resolved mass spectrometry has been studied. Mass spectrometry shows that the main positive ion species are Ca+, Mn+, La+, and LaO+. The Ca+ and Mn+ energy distributions are quite broad and lie in the 0–100 eV region, with the average energies increasing with laser fluence. In contrast, the La+ and LaO+ distributions are strongly peaked around 10 eV. The net time-of-arrival signal derived from the measured positive ion energy distributions is broadly consistent with the positive ion signal measured by the Langmuir probe. We also detected a significant number of O− ions with energies in the range of 0 to 10 eV. The Langmuir probe was also used to measure the temporal variation of the electron density and temperature at 6 cm from the ablation target. In the period when O− ions are found at this position, the plasma conditions are consistent with those required for significant negative oxygen ion formation, as revealed by studies on radio frequency excited oxygen plasma.
PUBLISHED
Keywords: Probe plasma diagnostics; Mass spectrometry; Mass spectrometers; Spectrum analysis; Laser ablation